Coherent interface driven super-plastic elongation of brittle intermetallic nano-fibers at room temperature. (10th July 2022) - Choi, Eun-Ae; Han, Seung Zeon; Kim, Hyung Giun; Ahn, Jee Hyuk; Lim, Sung Hwan; Kim, Sangshik; Hwang, Nong-Moon; Kim, Kwangho; Lee, Jehyun
Highlights: Coherent interface between Ni2 Si and Cu induce plastic deformation of Ni2 Si. Every ISFE has lower value than that of atomic bond breaking energy during slip. The super-coherency forms a number of new interfaces. Lattice tilting and poly-crystallization operate to release the strain on Ni2 Si. Abstract: The intermetallic compound such as Ni2 Si has a brittle nature. Therefore, monolithic intermetallic compounds have not yet been prepared by mechanical downsizing. During mechanical drawing of bulk Cu-Ni2 Si alloy at room temperature, we observed more than 400% plastic elongation of hard and brittle Ni2 Si intermetallic nano-fibers. The calculation based on the density functional theory reveals that the fully coherent interface induces strain on the intermetallic compound surrounded by the matrix, and lowers the intrinsic stacking fault energy below the level required to break an interatomic bond. The new interface between the Ni2 Si intermetallic and Cu matrix formed by the plastic deformation is as stable as the original coherent interface formed by precipitation, and the activation energy of the newly formed interface to slip is similar to that of the Cu matrix. All of these make plastic deformation of brittle Ni2 Si intermetallic possible by slip without failure. Graphical abstract: Image, graphical abstract